Հնչերանգը՝ որպես հորդորական ասույթների չնշույթավորված չափորոշիչ - Դավիթ Եպիսկոպոսյան (ՀՀ ԳԱԱ հրատ.)
Интонация как предложение-образующий элемент формирует окончательный вид побудительных изречений, передавая им соответствующий характер. Как надежный указатель интонация играет ключевую роль в распознании и выделении побудительных изречений, выполняя функции как семантического, так и прагматического компонентов, благодаря чему становится возможным различение разнообразных проявлений категории побуждения. Intonation as a sentence-constitutive element provides a final form to an inductive dictum according a persistence nature to the sentence. As a reliable indication intonation plays a key role in the recognition and allocation of inductive dictum fulfilling the functions of both semantic and pragmatic components. This makes possible to differentiate various manifestations of similar categories of inducement.
Keywords: Philology; Linguistics; Language and Literature